The impact of firm prestige on executive compensation - Focke, Florens; Maug, Ernst; Niessen-Ruenzi, Alexandra (Journal of Financial Economics, 2017)
We show that chief executive officers (CEOs) of prestigious firms earn less. Total compensation is on average 8% lower for firms listed in Fortune’s ranking of America’s most admired companies. We suggest that CEOs are willing to trade off status and career benefits from working for a publicly admired company against additional monetary compensation. Our identification strategy is based on matched sample analyses, difference-in-differences regressions, and a regression discontinuity design. We perform several robustness checks and exclude many alternative explanations, including that firm prestige just proxies for better corporate governance or for increased exposure of the pay-setting process to media attention.